The Potential of Polysaccharides from Various Plants as Constipation Treatment - Sari, Yuli Perwita; Candraruna, Dipta Bthari (Journal of Applied Food Technology, 2023)
Constipation is one of the disorders of Irritable Bowel Syndrome (IBS). Lack of consumption of water and food with fiber are some of the causes of constipation. Treatment for constipation patients can be solved by administering laxatives through drugs (pharmaceuticals) or using polysaccharide parts from plants. There are at least three types of laxatives: bulking agents (having the ability to bulk up), osmotic agents, and stimulants. Polysaccharides can be sourced from whole or some parts of the plants. Each type of plant has different polysaccharide components, and their effects on constipation treatment are also specific. The study aimed to review the mechanisms of polysaccharides from various plants parts and explained the misconception of polysaccharide intake as a laxative agent in treating constipation. This review was based on literature studies related to polysaccharides from plants materials and their effects as laxatives in experimental animals. The review found that these polysaccharides have a positive effect as a laxative or digestive aid. In general, polysaccharides from several plants were extracted and characterized to be used as anti-constipation test materials. These polysaccharides can help increase the amount, weight, and water content of feces (bulk), increase peristalsis, speed up gastric emptying and transit time, as well as restore hormones that work in movement in the digestive tract, and improve the condition of the distal colon tissue. These studies are still limited to using animals as experimental test material in polysaccharides to treat constipation. In addition, it has the potential to be further explored regarding the possibility of clinical trials of polysaccharides in humans as laxatives.